The Effectiveness of Cognitive Behavioral Therapy on Social Anxiety and Academic Procrastination in Adolescents - Rameshgar , Hanieh; Naghipour , Zeynab; Delfi , Ali; Fallahpour , Hediyeh; SamKhaniani, Eshagh (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective:  The present study aimed to determine the effectiveness of cognitive behavioral therapy on social anxiety and academic procrastination among adolescents.Methods and Materials: The present study employed a quasi-experimental design with a pretest–posttest structure and a control group. The statistical population consisted of adolescents who were referred to counseling and psychological services clinics in Tehran during 2025. Using convenience sampling, 30 adolescents were selected and randomly assigned into experimental and control groups, with 15 participants in each group. Data were collected using the Social Anxiety Scale for Adolescents and the Academic Procrastination Scale. After the pretest assessment, the experimental group participated in eight 90-minute sessions of cognitive behavioral therapy, while the control group continued their routine daily activities without intervention. At the completion of the intervention, both groups completed the posttest measures. Data were analyzed using descriptive statistics and analysis of covariance (ANCOVA) through IBM SPSS Statistics.Findings: The findings indicated that cognitive behavioral therapy had a significant effect on reducing social anxiety and academic procrastination among adolescents. After controlling for pretest scores, the results of analysis of covariance showed that the group effect on posttest social anxiety scores was statistically significant, F(1, 27) = 42.32, p < .001, η² = .62. Additionally, the group effect on academic procrastination scores was significant, F(1, 27) = 32.64, p < .001, η² = .57. The obtained effect sizes demonstrated that cognitive behavioral therapy produced substantial improvements in both psychological and academic functioning among participants in the experimental group compared to the control group.Conclusion: The results of the present study demonstrated that cognitive behavioral therapy is an effective intervention for reducing social anxiety symptoms and academic procrastination among adolescents.